The Effect Of Traditional Jamu Consumption On Liver Function In Pregnant Women In Rural Areas - Kasmara, Dwi Pratiwi; Pannyiwi, Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The use of traditional herbal medicine remains common practice in various rural areas of Indonesia, including among pregnant women. Jamu is considered an easily accessible, culturally based alternative healthcare treatment and is believed to provide benefits such as increasing stamina, reducing nausea, and alleviating pregnancy symptoms. However, some active herbal ingredients are known to be metabolized in the liver and have the potential to increase hepatocellular function, especially in specific physiological conditions such as pregnancy. This study aims to analyze the effect of traditional herbal medicine consumption on liver function in pregnant women in rural areas. The study used a cross-sectional design with a sample of 60 pregnant women in their second and third trimesters selected through a purposive sampling technique. Data were collected using a structured questionnaire regarding herbal medicine consumption patterns (type of herbal medicine, frequency, duration of consumption), then laboratory tests were conducted on liver enzyme levels SGOT and SGPT as indicators of hepatic function. As many as 40% of respondents were recorded as consuming herbal medicine regularly (≥3 times per week), with the most common types of herbal medicine being turmeric and tamarind, beras kencur, and temulawak. On average, respondents had had a habit of consuming herbal medicine long before pregnancy. Analysis using the Mann -Whitney test showed a significant difference in SGOT (p = 0.031) and SGPT (p = 0.038) levels between pregnant women who regularly consumed herbal medicine and those who did not. However, the median SGOT and SGPT values in the herbal medicine group remained within normal limits, thus not indicating clinical liver damage. However, this statistically significant increase indicates an additional metabolic burden on the liver due to exposure to the active ingredients of the herbal plant. This study concludes that consumption of traditional herbal medicine has the potential to affect liver function in pregnant women, although the effects have not yet reached pathological levels. Therefore, herbal medicine use during pregnancy should be done wisely, in a controlled manner, and in consultation with a healthcare professional. Further research with a longitudinal design, larger sample sizes, and laboratory analysis of herbal medicine ingredients is recommended to obtain a more comprehensive picture.